Psychoeducational Group With Problem Solving And Self Management Techniques To Improve Career Maturity (Universitas Negeri Semarang, 2020)
Career maturity is important since it enables students to choose the right career and prepare to enter workforce. Lack of career maturity will cause the students have no information about career or further study after graduation. Therefore, this study aimed to examine the effectiveness of psychoeducational group with problem solving and self-management techniques to improve the career maturity of 24 students of Public Vocational High School (SMK Negeri) in Semarang. This experimental study used randomized pretest posttest comparison group design. Based on Wilcoxon and Kruskal Wallis analysis results, the psychoeducational group with problem solving technique, self-management technique, and the combination of those techniques gained improvement in terms of career maturity. In details, the psychoeducational group with problem solving technique obtained better improvement than that of self-management and the combination of those techniques. Finally, this study recommends the use of problem-solving technique to improve the career maturity of Vocational High School students.